2015
DOI: 10.4018/ijdet.2015040104
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Game-Based Learning Efforts in Higher Education

Abstract: Though there is considerable research to support using Game-Based Learning (GBL) in higher education, its implementation is lagging behind K-12 education by an order of magnitude. By considering the current state of GBL from leadership, primary consumer, academic and technical perspectives, the authors frame the main issues involved with successfully implementing these efforts. These issues involve obtaining the resources required to make mature serious games that are similar in presentation, functionality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, the researcher calculated standard deviations, percentages, frequencies and means. Regarding the criteria employed to have the means in this study classified, they are shown below: Ghablan (2019), Keller (2008), Li (2017), Reinders, & Wattana (2015), Moylan (2015), and Turner et al (2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the researcher calculated standard deviations, percentages, frequencies and means. Regarding the criteria employed to have the means in this study classified, they are shown below: Ghablan (2019), Keller (2008), Li (2017), Reinders, & Wattana (2015), Moylan (2015), and Turner et al (2018).…”
Section: Discussionmentioning
confidence: 99%
“…It allows instructors to identify the extent of progress achieved by learners. However, the digital games must be related to the course content and goals (Moylan, 2015). It encourages learners to communicate with others and offer more opportunities to usethrough the second language.…”
Section: Advantages Of Using Digital Games For Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, gamebased learning can be considered as a functional teaching method that empower students to explore different parts of games as a form of learning process to help them enhance their set of skills or achieve specific learning outcomes. However, in designing game-based learning at university level, it is important to ensure that digital games are aligned with the course content and course objectives to achieve the effectiveness of game-based learning (Moylan et al, 2015). Previous studies have discussed the impact of game-based learning in the digital era, where several number of contemporary researches have already acknowledged the potential of digital games to capture student's attention in motivating them to explore the edges of their competence, skills and knowledge (Fokides, 2020;Megagianni and Kakana, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of, and need for, empirical studies which examine different game mechanics and their effects within courses is noted by Aguilar, Holman, and Fishman (2015). Higher Education has lagged behind school-based implementations of GBL, due to the barriers to adoption particular to this context (Moylan, Burgess, Figley, & Bernstein, 2015;Whitton & Moseley, 2012) and the difficulties of evaluating high-level cognitive outcomes (Whitton, 2012) resulting in little research addressing high-level, functional learning outcomes and less still specific to a postgraduate context. This paper analyses the development and evaluation of How to Fail Your Research Degree, an educational game for teaching postgraduate research skills.…”
Section: Introductionmentioning
confidence: 99%